Mediterranean agroindustrial wastes as valuable substrates for lignocellulolytic enzymes and protein production by solidstate fermentation - Salgado, José Manuel (2018)
BACKGROUND: Mediterranean agrofood industries, among which are wineries, breweries and olive mills, dispose a great amount of wastes, which generate environmental problems and have a low nutritional value to be used as animal feed. In this sense, solidstate fermentation (SSF) can increase the nutritional value of these wastes and simultaneously produce lignocellulolytic enzymes. RESULTS All fermented wastes were enriched in protein by the three fungi studied. A. ibericus was the fungus with the biggest increase of protein, which ranged from 1.4 times to 6.2 times respect to unfermented wastes. Likewise, A. ibericus achieved the maximum cellulase and xylanase activities. The relationship among substrates composition, fungi used and SSF performance were evaluated by PCA analysis. The high content of cellulose and hemicellulose favoured the lignocellulolytic enzymes production and the phenolics content were negatively correlated with enzymes production and with the increase of protein by SSF. Furthermore, the scanning electron microscopy analysis showed the growth of fungi over solid wastes, the formation of conidiophores and the changes in their structures. CONCLUSION The nutritional value of Mediterranean wastes was improved and other valueadded products as lignocellulolytic enzymes were produced in the same process, which could facilitate the efficient reuse of these wastes.